1996
DOI: 10.5694/j.1326-5377.1996.tb138683.x
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne disease: current trends and future surveillance needs in Australia

Abstract: Review of 128 outbreaks of foodborne disease (affecting almost 6000 people, with six deaths) between 1980 and 1995 and available surveillance data showed that foodborne disease in Australia is similar to that in other industrialised countries. Campylobacter spp. and non‐ typhoidal Salmonella spp. were the most commonly reported pathogens. However, Australia, unlike the UK and US, lacks a comprehensive national surveillance system for foodborne diseases. This is essential to improve control of these diseases. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 1 publication
(1 reference statement)
0
14
0
Order By: Relevance
“…[29][30][31] Although its incidence in Australasia is not known, a retrospective study of outbreaks of foodborne disease reported to the National Notifiable Diseases Surveillance System between 1980 and 1995 in Australia showed that 7% were caused by S. aureus. 32 However, because many cases of SFD may not seek medical attention or come to the notice of public health authorities, it is likely that the true incidence of SFD is significantly greater that that estimated from investigations of suspected foodborne disease outbreaks.…”
Section: Non-menstrual-related Toxic Shock Syndrome (Nmtss)mentioning
confidence: 99%
“…[29][30][31] Although its incidence in Australasia is not known, a retrospective study of outbreaks of foodborne disease reported to the National Notifiable Diseases Surveillance System between 1980 and 1995 in Australia showed that 7% were caused by S. aureus. 32 However, because many cases of SFD may not seek medical attention or come to the notice of public health authorities, it is likely that the true incidence of SFD is significantly greater that that estimated from investigations of suspected foodborne disease outbreaks.…”
Section: Non-menstrual-related Toxic Shock Syndrome (Nmtss)mentioning
confidence: 99%
“…For FBD outbreaks with a known pathogen, the most commonly identified cause was Salmonella, which is consistent with Australian and international findings. [7][8][9] The most common setting in which foods were prepared were restaurants and takeaways and the most commonly implicated food vehicle was poultry. Insufficient cooking, inadequate refrigeration, cross contamination from raw ingredients, and food handler contamination, were common factors associated with FBD outbreaks during this period.…”
Section: Discussionmentioning
confidence: 99%
“…First, surveillance data are likely to substantially under-represent the number of people with CEDs in NSW, as many people with gastroenteritis may not present to a medical practitioner. 9 The proportion of those that do present and then have a stool sample taken is also unknown, but is likely to be small. Second, the outbreak data may be incomplete because many outbreaks, especially if small and self-limited, may not be reported to public health units.…”
Section: Discussionmentioning
confidence: 99%
“…Listeria monocytogenes is a Gram-positive intracellular bacterial pathogen that is the causative agent of listeriosis1. The unique ability of L. monocytogenes to cross several tight barriers within the infected human host contributes to its pathogenesis, leading to high hospitalisation and fatality rates12.…”
mentioning
confidence: 99%
“…The unique ability of L. monocytogenes to cross several tight barriers within the infected human host contributes to its pathogenesis, leading to high hospitalisation and fatality rates12. This food-borne pathogen is especially dangerous in pregnant women, newborns, and the immunocompromised3, with current treatments for listeriosis generally consisting of a combination of supportive and antibiotic therapies.…”
mentioning
confidence: 99%